Uneven adoption of dialogic communication on hotel websites: evidence from Portuguese world travel award nominees - Oliveira, Adriana; Oliveira, Helena Costa; Giuliani, Gabriela; Estrada, Rita (Frontiers in Human Dynamics, 2026)
In the context of digital communication, organizations use websites to interact with their audiences, particularly between hotel establishments and the public. This dialogue can be achieved by adopting dialogic principles, allowing greater interactivity and promoting two-way communication. The aim of this article is to study the degree of adoption of the dialogic cycle, identifying the most frequently used indicators to establish communication with customers and to build and sustain relationships. To this end, the study analyzed the websites of the Portuguese hotels nominated for the World Travel Awards 2023, both individually and by category: Best Hotel, Best Resort, and Best Boutique. The findings show that websites are a favored means of communication between hotels and the public. However, a discrepancy was observed in the adoption of dialogic indicators: while means of contact and links to social networks registered 100 per cent adoption, indicators such as questionnaires (feedback) and customer experiences sharing registered almost zero adoption. Although the differences were not significant, the “Best Hotel” category showed a higher level of adoption of the dialogue principle. This study contributes to the understanding of how dialogic cycle can enhance organizational-customer relationships, highlighting its potential to foster more meaningful and interactive communication in the hospitality sector.